Analisis Pertumbuhan Ekonomi, Kemiskinan dan Korupsi di Indonesia di Negara ASEAN Lower Middle Income - Riska Dewi Putri; Hasdi Aimon (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
This study aim to indentify and analyze responses economic growth, poverty and corruption in ASEAN lower middle income countries. Type of this research is descriptive and associative, used a secondary panel data from 2010 to 2017. This research was conducted using the Vector Autoregression (VAR) model through the analysis of Impulse Response Funtion (IRF) and Variance Decomposition (VD) to determine the variability response of a particular variable due to the shock of other variables. The results of this study indicate that: (1) Variability of economic growth is not contributed by the shock of poverty and corruption in the short term, but in the long run the variability of economic growth is contributed by the shock of poverty and corruption. (2) In the short variability of poverty is not contributed by the shock of economic growth and corruption term, but in the long run economic growth and corruption contribute to influencing poverty variability. (3) The variability of corruption is contributed by the shock of economic growth and poverty in the short and long term.